Faktor Risiko yang Berhubungan dengan Hipertensi pada Jemaah Haji Embarkasi Banjarmasin Kalimantan Selatan 2024 - Nani, Nani; Helda, Helda; Raf Raf, Khansa (Jurnal Epidemiologi Kesehatan Indonesia, 2024)
Hypertension is a silent killer that is a major contributor to deaths worldwide every year. Hypertension is identified as one of the comorbidities that are often found in pilgrims. Various risk factors can play a role in the occurrence of hypertension. The purpose of this study is to analyze the risk factors that most significantly contribute to hypertension in Banjarmasin embarkation pilgrims in 2024. The research was carried out with a cross sectional design that utilizes secondary data sourced from the Integrated Hajj Computerized System related to health services during Hajj. The proportion of hypertension in Banjarmasin embarkation pilgrims in 2024 is 41.75%.. Multivariate analysis using cox regression revealed that the most significant risk factors contributing to hypertension were the variables of age ≥80 years (Pvalue=0.000) and adjusted PR of 5.36 (95%CI: 3.92-7.33), age 60-79 years (Pvalue=0.000) and adjusted PR value of 4.63 (95%CI: 3.79-5.65), age 41-59 years (Pvalue=0.000) and adjusted PR value of 3.18 (95%CI: 2.62-3.85), The central obesity variable (p=0.000) and adjusted PR value of 61.25 (95%CI; 1.15-1.36), the diabetes mellitus variable (p=0.000) and the adjusted PR value of 1.22 (95%CI; 1.09-1.35), the family hypertension history variable (p=0.000) and the adjusted PR value of 1.52 (95%CI; 1.39-1.65). Understanding the risk factors associated with hypertension is very important as an optimal effort to prevent and control hypertension so that it can reduce the prevalence of hypertension among pilgrims.